Country-level predictors of vaccination coverage and inequalities in Gavi-supported countries. Issue 18 (25th April 2017) - Arsenault, Catherine; Johri, Mira; Nandi, Arijit; Mendoza Rodríguez, José M.; Hansen, Peter M.; Harper, Sam
Highlights: Important differences remain in vaccination coverage and inequalities across countries. This study investigates country-level factors associated with vaccination coverage and equity. Political stability, gender equality and smaller land areas were important predictors. Low out-of-pocket spending & high external resources were associated with improved equity. Higher government spending & low linguistic fractionalization were consistent with better vaccination outcomes. Abstract: Background: Important inequalities in childhood vaccination coverage persist between countries and population groups. Understanding why some countries achieve higher and more equitable levels of coverage is crucial to redress these inequalities. In this study, we explored the country-level determinants of (1) coverage of the third dose of diphtheria-tetanus-pertussis- (DTP3) containing vaccine and (2) within-country inequalities in DTP3 coverage in 45 countries supported by Gavi, the Vaccine Alliance. Methods: We used data from the most recent Demographic and Health Surveys (DHS) conducted between 2005 and 2014. We measured national DTP3 coverage and the slope index of inequality in DTP3 coverage with respect to household wealth, maternal education, and multidimensional poverty. We collated data on country health systems, health financing, governance and geographic and sociocultural contexts from published sources. We used meta-regressions to assess the relationship between these country-level factors and variations in DTP3 coverage and inequalities. To validate our findings, we repeated these analyses for coverage with measles-containing vaccine (MCV). Results: We found considerable heterogeneity in DTP3 coverage and in the magnitude of inequalities across countries. Results for MCV were consistent with those from DTP3. Political stability, gender equality and smaller land surface were important predictors of higher and more equitable levels of DTP3 coverage. Inequalities in DTP3 coverage were also lower in countries receiving more external resources for health, with lower rates of out-of-pocket spending and with higher national coverage. Greater government spending on heath and lower linguistic fractionalization were also consistent with better vaccination outcomes. Conclusion: Improving vaccination coverage and reducing inequalities requires that policies and programs address critical social determinants of health including geographic and social exclusion, gender inequality and the availability of financial protection for health. Further research should investigate the mechanisms contributing to these associations.